1995
DOI: 10.1161/01.str.26.12.2285
|View full text |Cite
|
Sign up to set email alerts
|

Can Cerebrovascular Reactivity Be Measured With Near-Infrared Spectroscopy?

Abstract: NIRS signal changes in HbO2, Hb, and total hemoglobin concentration are very sensitive to alterations in EtCO2, which are largely independent of extracranial tissue perfusion. NIRS may be developed as an alternative method for testing cerebrovascular reactivity and may be of particular clinical importance when the ultrasound window is poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
121
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(135 citation statements)
references
References 38 publications
12
121
2
Order By: Relevance
“…However, reactivity and diameter changes have been demonstrated in the fetus and newborn (20,21), bringing into question the validity of the TCD technique. Our findings and those of others (22,23) suggest a correlation between measurements made by NIRS and TCD.…”
Section: Discussionsupporting
confidence: 88%
“…However, reactivity and diameter changes have been demonstrated in the fetus and newborn (20,21), bringing into question the validity of the TCD technique. Our findings and those of others (22,23) suggest a correlation between measurements made by NIRS and TCD.…”
Section: Discussionsupporting
confidence: 88%
“…Changes in cerebral blood flow velocity in this frequency range are believed to represent autoregulatory compensatons to slow hemodynamic oscillations. [34][35][36] Our results support our prior findings showing that NIRS can be exploited for autoregulation monitoring. 16,24,37,38 In a piglet laboratory model we found that cerebral oximetry index was significantly correlated with cerebral blood flow autoregulation monitoring based on laser Doppler methods.…”
Section: Discussionsupporting
confidence: 90%
“…In one study (40), increases in cutaneous blood flow have been reported. We here observe that both the NIRS signals from the cheek and cutaneous plethysmography (forehead) detected increase in blood volume in a large percentage of cases, all these signals being moderately correlated with tHbi.…”
Section: Hvmentioning
confidence: 95%